A Cross-Sectional Approach in Unveiling the Prevalence, Anthropometric Measurements, and Risk Factors of Eating Disorders among Bengalee Adolescent Females - Saha, Shaonee; Biswas, Reetapa (Anthropological Review, 2025)
Background: The crucial adolescent period demands greater nutritional needs along with physical maturity where overweight can lead to sensitivity towards body image. Excessive appearance concern results in faulty eating habits and complementary behavioral approaches known as eating disorders (ED). Aim: Due to inconsistencies in prior information regarding ED on Bengalee adolescent females, the cross-sectional study was conducted on Bengalee school females of rural and urban areas of North 24 Parganas district with the insights of prevalence, anthropometric parameters and risk factors of ED. Method: The study design consisted of self-reported surveys using standardized questionnaires (Eating disorder examination questionnaire-28; Body shape questionnaire-34) to determine ED, body dissatisfaction (BD), meal skipping (MS) and objective assessments of anthropometric parameters of 396 students aged 13–19 years. Statistical analysis was conducted to interpret the findings. Result: 14.39% ED and 44.95% BD cases were found in this community with significantly high BMI-for-age (BAZ), hip circumference and subscale values of ED questionnaire among ED participants. After chi-square and binary logistic regression analysis regular MS was found to be the strongest predictor of ED accounting for 14% likelihood of ED followed by fear-of-weight-gain (4.48%) and excessive exercise (3.88%). Conclusion: The findings highlight a complex interplay of psychological and social factors contributing to ED. Regular MS emerged as the strongest predictor of ED, reflecting an unhealthy coping strategy driven by psychological stressors such as fear of weight gain, excessive exercise and BD. Influence of cultural norms on body image cannot be avoided. Our findings will help healthcare practitioners in designing identification treatment procedures and diet plans in a holistic way during further investigation of ED.